Transcriptomic insights into fate choice of pallial versus subpallial GABAergic neurons - Lijuan Sun; Feng Xiong; Feier Huang; Shuangshuang Dong; Pei Zhu; Pengfei Jiang; Baoshen Zhang; Xinxin Zhang; Jie Sun; Hanchuan Peng; Chunjie Zhao (Nature Communications)
Abstract The activity of the telencephalon is shaped by pallial and subpallial GABAergic neurons, two large populations produced in the embryonic ganglionic eminence. However, knowledge about the fate specification of neuron subtypes is limited, especially whether there is a common mechanism directing the fate choice of pallial versus subpallial populations remains unknown, largely because each population comprises numerous subtypes. Here, using sc-RNA sequencing combined with loss-of-function we profile ganglion eminence lineages and find that Foxg1 deletion causes the pallial population to adopt subpallial fates in mice. We delineate developmental trajectories and reveal FOXG1-driven transcriptional programs that specify neuron subtypes in each GE lineage and transcription factors that direct lineage bifurcation decisions. We uncover a common mechanism that drives pallial fate over subpallial fate across ganglion eminence lineages. Our study illuminates the control of production between pallial and subpallial populations and offers transcriptomic insights into the pathogenesis of GABAergic neuron-related disorders.